Evisceration with autogenous scleral graft and bioceramic implantation within the modified scleral shell: 133 cases over 17 years. (2nd January 2019) - Nadal, Jeremy; Daien, Vincent; Jacques, Jérôme; Hoa, Didier; Mura, Frederic; Villain, Max
ABSTRACT: Introduction : To present long-term follow-up data on evisceration performed with autogenous scleral grafting and ceramic implantation in a modified scleral shell. Methods : This was a retrospective analysis of all consecutive eviscerations performed in the Department of Ophthalmology, Montpellier University Hospital, France, between February 1998 and October 2015. For all patients, the technique used was a conventional anterior evisceration after total keratectomy, disinsertion of the medial rectus muscle, sectioning of the optic nerve and excision of sclera centered on the papilla. The scleral graft was then sutured just behind the sutured keratectomy, and the bioceramic implant was inserted by posterior way in the scleral shell. Demographic characteristics, implant size and type, cosmetic results from pictures of all patients and complications were recorded. This study was performed with Ethics Review Committee Approval, and in compliance with the Declaration of Helsinki. Results : In total, 133 patients (36.6% women) were identified during the study period. The mean (SD) implant size was 17.32 (1.84) mm. The median follow-up after evisceration was 57.43 (24.7, 68.3) months. Two cases of implant exposure (1.5%) were recorded. For 24 patients (17.9%), additional surgeries were performed for ptosis (2.2%), conjunctival cyst (1.5%), or post-evisceration socket syndrome (6.7%). Cosmetics results were excellent for 50.1% of cases, good for 33.3% and fair for 16.6%; using a grading scale based on the superior sulcus deformity. Conclusion : Evisceration with autogenous scleral grafting and ceramic implantation can result in a high volume of restoration, good cosmetic results, and low risk of exposure of the implant.